What is the Diagnosis? - Pacheco, Júlio Cota; Knust, Beatriz Silvestre; Leme, Jonas Paes; Santos, Hercilia S. C. A. (JOURNAL OF CARDIAC ARRHYTHMIAS, 2020)
The tracings obtained in long-term electrocardiographic monitoring by the Holter system.